Dzieciństwo i edukacja dzieci w Chinach w perspektywie nierówności społecznych - Mańkowska, Anna (Wydawnictwo Naukowe UAM, 2016)
This article studies the meaning of childhood and educational chances for children in modern China during unequal economic growth. The article starts with showing the Confucian traditional meaning of having and being children and explains the understanding and practice of the one)child policy in China. Moreover the article presents a new family model which causes a new understanding of childhood. It shows also how China’s unequal economic growth encourages large-scale urban migration and what the educational effects of such a labor movement are. The article moreover pinpoints crucial changes in the Chinese cultural values system and shows how it affects the schooling and caring system for Chinese citizens.
Childhood and Early Education in China in the Social Inequality Perspective
Keywords: China; education; childhood; urban migration